2009
DOI: 10.1038/ng.485
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies common variants at four loci as genetic risk factors for Parkinson's disease

Abstract: To identify susceptibility variants for Parkinson's disease (PD), we performed a genome-wide association study (GWAS) and two replication studies in a total of 2,011 cases and 18,381 controls from Japan. We identified a new susceptibility locus on 1q32 (P = 1.52 x 10(-12)) and designated this as PARK16, and we also identified BST1 on 4p15 as a second new risk locus (P = 3.94 x 10(-9)). We also detected strong associations at SNCA on 4q22 (P = 7.35 x 10(-17)) and LRRK2 on 12q12 (P = 2.72 x 10(-8)), both of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
600
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,190 publications
(633 citation statements)
references
References 41 publications
18
600
1
2
Order By: Relevance
“…Recently, our understanding of idiopathic PD has been enhanced by genome‐wide association (GWA) studies6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 that have collectively identified PD risk variants at >18 loci 6, 7. Despite their high levels of significance, these 18 loci are thought to account for only a very small amount (3–5%) of the expected heritability of PD 17.…”
mentioning
confidence: 99%
“…Recently, our understanding of idiopathic PD has been enhanced by genome‐wide association (GWA) studies6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 that have collectively identified PD risk variants at >18 loci 6, 7. Despite their high levels of significance, these 18 loci are thought to account for only a very small amount (3–5%) of the expected heritability of PD 17.…”
mentioning
confidence: 99%
“…Missense mutations and locus multiplications in the SNCA gene, which encodes the protein α-synuclein, have been found to cause familial forms of PD. [1][2][3][4][5] Genome wide association studies (GWAS) have shown that polymorphisms in the SNCA gene are risk factors for developing sporadic PD [6][7][8][9] and aggregated α-synuclein is the main component of Lewy bodies, the protein inclusions prevalent in the brains of patients with PD. 10 Furthermore, overexpression of α-synuclein has been found to be toxic to dopaminergic neurons, implicating α-synuclein as a key player in the molecular mechanisms of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent genome-wide association studies on PD found that a common variant in five genes, including ␣-synuclein and MAPT, which increase disease susceptibility (31,32). Moreover, an earlier study indicated that the cognitive decline and development of PD dementia is strongly associated with a synergistic interaction between the MAPT inversion polymorphism and a single nucleotide polymorphism on the ␣-synuclein gene (33).…”
mentioning
confidence: 99%